Paraplegia after percutaneous iliac stenting: How did that happen? - Emre Ozdemir; Mustafa Karaca; Ayşen Suzen Ekinci (KARE Publishing, 2019)
Paraplegia after percutaneous iliac angioplasty is very rare, and is typically associated with spinal cord ischemia (SCI). Presently described is a case of SCI and paraplegia developing after bilateral iliac stenting. This complication may be caused by a change in spinal blood flow in patients with diffuse atherosclerosis, and should be kept in mind.